Impact of UV radiation on Mxene-mediated tubulin dissociation and mitochondrial apoptosis in breast cancer cells. - Tan, Ee Wern *; Simon, Samson Eugin; Arshid, Numan *; Khalid, Mohammad *; Tan, Kuan Onn * (Elsevier, 2024)
Breast cancer is a global health concern that requires personalized therapies to prevent relapses, as conventional treatments may develop resistance over time. Photothermal therapy using spectral radiation or intense light emission is a broad-spectrum treatment that induces hyperthermia-mediated cancer cell death. MXene, a two-dimensional material, has been reported to have potential biological applications in photothermal therapy for cancer treatment. In this study, we investigated the apoptotic activity of MXene and UV-irradiated MXene in MCF-7 breast cancer cells by treating them with varying concentrations of MXene. The cytotoxicity of MXene and UV was evaluated by analyzing cellular morphology, nuclei condensation, caspase activation, and apoptotic cell death. We also assessed the effect of the combined treatment on the expression and cellular distribution of Tubulin, a key component of microtubules required for cell division. At low concentrations of MXene (up to 100 µg/ml), the level of cytotoxicity in MCF-7 cells was low. However, the combined treatment of MXene and UV resulted in a synergistic increase in cytotoxicity, causing rounded cellular morphology, condensed nuclei, caspase activation, and apoptotic cell death. Furthermore, the treatment reduced Tubulin protein expression and cellular distribution, indicating a potent inducer of cell death with potential application for cancer treatment. The study demonstrates that the combined treatment of MXene and UVB irradiation is a promising strategy for inducing apoptotic cell death in breast cancer cells, suggesting its potential as a therapeutic intervention for breast cancer.